Towards Continuous Organic Photochemistry - Flinn, Amy (2021)
The work presented in this Thesis is motivated by an increasing interest in approaching Chemistry from a greener standpoint. This work is focused on improving reaction credentials through a photochemical and/or flow approach, which despite the increasing uptake of these methods in academia is still limited in industry. This is, in part, due to misconceptions around the ease, applicability and scalability of these methods. This Thesis describes the investigation of various chemical transformations to continuous photochemical approaches, including exploiting unique reactors and flow equipment available at Nottingham. The reactions investigated include photoborylation, the Fries rearrangement and ozonolysis, which were selected due to their widespread use in drug synthesis.